2015
DOI: 10.1074/jbc.m115.675579
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligases, HUWE1 and NEDD4-1, Are Involved in the Post-translational Regulation of the ABCG1 and ABCG4 Lipid Transporters

Abstract: Background:The ABCG1 lipid transporter is regulated via protein ubiquitination. Results: We identify two E3 ligases that regulate the protein stability and activity of ABCG1 and ABCG4. Conclusion: The ligases, HUWE1 and NEDD4-1, are involved in the regulation of cholesterol export from cells. Significance: Understanding the fine tuning of cholesterol homeostasis will help to understand how dysregulation can cause disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 44 publications
0
44
2
Order By: Relevance
“…Furthermore, the observations that both cholesterol efflux inhibition and ABCA1 depletion were prevented by down-regulation of Par1 or disruption of its gene suggest that Par1 mediates the effects of thrombin on cholesterol efflux and ABCA1 levels in both macrophages and smooth muscle cells. Some reports showed that the ABC transporters, particularly ABCA1 and ABCG1, were vulnerable for ubiquitination and degradation affecting cholesterol efflux (46,47). Although a few studies have shown a role for ubiquitination in the degradation of ABCA1 and ABCG1, the underlying mechanisms, particularly the role of E3 ubiquitin ligases in these effects, have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observations that both cholesterol efflux inhibition and ABCA1 depletion were prevented by down-regulation of Par1 or disruption of its gene suggest that Par1 mediates the effects of thrombin on cholesterol efflux and ABCA1 levels in both macrophages and smooth muscle cells. Some reports showed that the ABC transporters, particularly ABCA1 and ABCG1, were vulnerable for ubiquitination and degradation affecting cholesterol efflux (46,47). Although a few studies have shown a role for ubiquitination in the degradation of ABCA1 and ABCG1, the underlying mechanisms, particularly the role of E3 ubiquitin ligases in these effects, have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Taking this rapid loss into account, the further disappearance of much of the rest of endogenous ABCG1 and GFP-G1 ( Fig 4 ) by 4-6h indicates that the remaining transporter is also not long-lived and is being lost at a rate that is quite rapid compared to recycling cell surface receptors such as TfR and the LDL receptor ( Fig 4 versus [ 50 , 51 ]). Thus, while ABCG1 is transported at appreciable levels in the β cell’s secretory and endocytic pathways, we suspect that its trafficking may be biased by sorting or modifications (e.g., ubiquitylation [ 52 ]) that favor lysosomal degradation over constitutive recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Taking this rapid loss into account, the further disappearance of much of the rest of endogenous ABCG1 and GFP-G1 (Fig 4) by 4–6h indicates that the remaining transporter is also not long-lived and is being lost at a rate that is quite rapid compared to recycling cell surface receptors such as TfR and the LDL receptor (Fig 4 versus [47,48]). Thus, while ABCG1 is transported at appreciable levels in the β cell’s secretory and endocytic pathways, we suspect that its trafficking may be biased by sorting or modifications (e.g., ubiquitylation [49]) that favor lysosomal degradation over constitutive recycling.…”
Section: Discussionmentioning
confidence: 99%